Sentiment Analysis of Student’s Perspectives on the Integration of a Mobile Fitness Application in a Physical Education Course Using Machine Learning Techniques - Dela Rosa, Aaron Paul Mallari; Abad, Rawil Paul Pama (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – With the intention of encouraging physical exercise and overall well-being among university students, the usage of mobile fitness applications in higher education has received attention. Bulacan State University (BulSU)-Meneses Campus, an HEI situated in Bulakan, Bulacan, offers different programs that take Physical Activity Towards Health and Fitness (PATHFit) courses. Students taking PATH-Fit courses at BulSU-Meneses used a mobile fitness application in their classes. Method – The study used qualitative sentiment analysis to determine the students’ sentiments toward integrating a mobile fitness application into their PATHFit course. The Support Vector Machine (SVM) algorithm was utilized to analyze and predict the sentiments on the annotated data. Results – On accomplishing paper-based forms, 191 out of 347 students tend to have more difficulty tracking and computing necessary fitness details, felt the hassle of accomplishing the forms rather than focusing more on exercising, and papers are easily misplaced or lost. With an accuracy of 91.34% and a class precision of 91.50% on the algorithm’s predicted positive sentiments, 313 out of 347 students were more focused on their activities using a mobile fitness application. Conclusion – In summary, the contrasting sentiments of students toward traditional, paper-based forms and the integration of a mobile fitness application show the power of technology in enhancing their experiences. As the landscape of fitness tracking continues to evolve, embracing technology is key to unlocking the potential of students in learning. Recommendations – In this light, BulSU, its other campuses, and other HEIs should consider implementing and integrating the same and other related fitness applications to technologically advanced pedagogical approaches in the university. Research Implications – Considering the results, this implies that students tend to accept the use of a fitness application integrated with their physical education course through their positive sentiments on using the application.